Gender-based constraints and opportunities to women's participation in the small ruminant value chain in Ethiopia: A community capitals analysis. Issue 3 (27th May 2017) - Mulema, Annet Abenakyo; Farnworth, Cathy Rozel; Colverson, Kathleen Earl
Abstract: Using the Community Capitals Framework, this article explores the factors enhancing or constraining women's access to, and control over, the resources required to participate in, and benefit from, small ruminant value chain activities. This is associated with the relationship of women and men to stocks of capitals: social, financial, human, natural, political, cultural, and physical, and how the relationship between various capitals is managed. Our data were collected using semi-structured interviews and focus group discussions in six woredas (districts) in different parts of Ethiopia. Our findings show that men and women are constrained by similar capitals, but women are more constrained by lower levels of the seven capitals. The sheep value chain has more opportunities for women. It is important to strengthen women's access to, and management of, all these capitals to become more effective managers of small ruminants. This demands behavioral change and working to challenge gender norms.